Naringin prevents heart mitochondria dysfunction during diabetic cardiomyopathy in rats - Ilya Zavodnik; Tatsiana A. Kavalenia; Siarhei N. Kirko; Elena B. Belonovskaya; Irina A. Kuzmitskaya; Yulia V. Eroshenko; Elena A. Lapshina; Vyacheslav U. Buko (ADMET and DMPK)
Background and purpose: Cardiac mitochondria dysfunction plays a central pathophysiological role in the abnormal glucose metabolism in the heart and in diabetic cardiomyopathy. The present study evaluated the effects of flavonoid glycoside naringin treatment on the interconnection between changes in cardiac mitochondria oxygen consumption, membrane potential and mitochondrial Ca2+ sensitivity during type 1 diabetes. Experimental approach: Type 1 diabetes was induced by an intraperitoneal injection of streptozotocin (40 mg/kg) in rats and islet morphology, glucose and insulin levels, changes in heart mitochondria respiration, membrane potential, spontaneous and Ca2+ - induced mitochondrial permeability transition (MPT) pore opening were evaluated. Key results: Diabetes resulted in typical signs of hyperglycemia, which were accompanied by a rat cardiac mitochondria dysfunction, manifested by decreased V2 and V3 rates of oxygen consumption, while the initial membrane potential value remained unchanged. The rates of Ca2+-induced MPT pore opening and Ca2+-induced membrane potential dissipation in isolated mitochondria decreased under type 1 diabetes. The naringin treatment (40 mg/kg of the body weight, 4 weeks) partially recovered impaired cardiac mitochondria respiration, decreased spontaneous and increased Ca2+-induced MPT pore opening, improved pancreatic islets morphology and dystrophic changes, lowered glycated hemoglobin and blood plasma urea, and decreased the oxidative stress level with glucose or insulin concentrations remaining unchanged in diabetic animals. Conclusions: Naringin administration demonstrated beneficial effects during type 1 diabetes and represents a promising therapeutic (or nutriceutical) approach for diabetes treatment.